Analysis of Clozapine Use and Safety by Using Comprehensive National Data From the Japanese Clozapine Patient Monitoring Service. Issue 4 (August 2018) - Inada, Ken; Oshibuchi, Hidehiro; Ishigooka, Jun; Nishimura, Katsuji
Abstract: Objective: The aim of this study was to investigate clozapine use and its associated adverse effects in patients in Japan. Methods: We analyzed data recorded from July 2009 to January 2016 (N = 3780 patients) in the Clozaril Patient Monitoring Service, which was established in Japan in 2009 and includes all Japanese patients who have been prescribed clozapine. Results: The treatment discontinuation rate was 23.9% (869/3780 cases). The average ± SD treatment duration was 234.9 ± 306.9 days (median, 115 days), and the average ± SD dosage was 186.41 ± 151.6 mg/d. The estimated treatment continuation rates resulting from all-cause discontinuation were 78.2 after 1 year and 72.9% after 2 years of treatment. The incidence of neutropenia/leucopenia was 5.4% (206/3780 cases). The average ± SD dose before discontinuation was 233.36 ± 168.15 mg (median, 200 mg; range, 4–600 mg). The incidence of glucose intolerance was 15.4% (583/3780 cases). Of 3780 patients, 98 (2.67%) developed glucose intolerance before and after taking clozapine administration, whereas 485 patients (12.8%) developed glucose intolerance after taking clozapine. The average ± SD time from treatment initiation to new onset of glucose intolerance was 382.2 ± 420.2 days (median, 216 days; range, 4–2053 days). Conclusions: The data obtained in this study, particularly regarding the incidence of clozapine-induced adverse events, will enable the optimal and safe use of clozapine in Japanese patients with treatment-resistant schizophrenia.